THE ROLE OF ASSISTANT TECHNOLOGY IN MEDIATION OF LEARNING: Challenges and Perspectives for the Practice of Inclusive Teaching - Barbosa, Sandra Regina; Orrico, Helio Ferreira [UNESP]; Fernandes, Ediclea Mascarenhas (Univ Estado Rio De Janeiro, 2024)
The rise of technologies and telecommunications has profoundly transformed the dynamics of communication, information and, especially, the learning process. With the introduction of new languages, means of communication and methodologies, the role of the teacher transcends the traditional teacherstudent relationship, starting to encompass the interconnection between teacher, knowledge and student. The teacher is no longer seen merely as a transmitter of knowledge, but rather as an active mediator, a facilitator who promotes, encourages and motivates learning, actively collaborating to achieve the learner's goals. In this context, this study aims to present and discuss how new methodologies and resources, specifically Assistive Technology (AT), can contribute to improving the learning experience, involving both teachers and students. Using an exploratory bibliographic research approach, we seek to enrich the reflective understanding of the topic. The research results indicate that resources and services characterized as Assistive Technology offer a variety of pedagogical strategies that can optimize teachers' practices as mediators of the educational process. These resources are often crucial to overcoming physical and attitudinal barriers that can hinder schooling, curricular adaptations and student development. However, in relation to teacher training processes, there is a need for innovations and new dynamics to maximize the use of these technologies, which is one of the main concerns for the development of inclusive practice.
Keywords: Assistive Technology; Inclusive education; Pedagogical Mediation; Continuing Training